A bainite high carbon semi-steel centrifugal composite roller ring
By optimizing the casting mold treatment, molten steel composition and heat treatment process, a matrix structure dominated by bainite is formed, which solves the problem of insufficient hardness and strength of the existing high-carbon semi-steel centrifugal composite roller ring, and significantly improves the tensile strength, hardness and wear resistance of the roller ring.
Patent Information
- Application Number
- CN202411956214.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-carbon semi-steel centrifugal composite roller rings have poor wear resistance and short life due to insufficient tissue hardness and strength of pearlite matrix.
Bainite high-carbon semi-steel material is used to optimize cast mold treatment, molten steel composition and heat treatment process to form a matrix structure mainly based on bainite to improve the tensile strength and hardness of the roller ring.
It significantly improves the tensile strength, hardness and wear resistance of the roller ring, extends the service life, and improves the rolling efficiency and steel quality.
Smart Images

Figure CN119747609A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material processing, in particular to a bainite high-carbon semi-steel centrifugal composite roller ring. Background Art
[0002] In modern steel production, H-shaped steel is a high-strength, lightweight construction and industrial material. Its production process requires multiple high-load rolling of steel in the rolling mill. The centrifugal composite roller ring in the rolling mill is a key component that directly contacts the steel and withstands high temperature, high pressure and high friction. Its performance directly affects the rolling efficiency, steel quality and production cost.
[0003] The high-carbon semi-steel centrifugal composite roller ring in the existing technology is widely used in rolling mills. It mainly adopts a matrix structure design with pearlite as the main component, realizes the composite structure of the working layer and the supporting layer through the centrifugal casting process, and combines the traditional heat treatment process to improve the material properties. This type of roller ring has good toughness and certain wear resistance, which meets the use requirements of general rolling conditions. In addition, the centrifugal casting technology can effectively utilize the centrifugal force distribution characteristics of molten steel, with high molding accuracy, and is suitable for the production of large-size or complex-structure composite roller rings.
[0004] However, there are many deficiencies in the materials and process design of the centrifugal composite roller ring in the prior art, mainly manifested in the insufficient hardness and strength of the matrix structure dominated by pearlite, which makes the roller ring easy to wear and have a short life under high load conditions; at the same time, improper control of key parameters such as rotation speed and pouring speed in the centrifugal casting process can easily lead to problems such as uneven thickness distribution of the inner and outer layers and interface bonding defects, limiting the use of the roller ring in scenarios with higher strength requirements; in addition, the existing heat treatment process fails to fully optimize the cooling control and tempering process of the metallographic structure transformation, resulting in uneven material microstructure and insufficient release of residual stress, which reduces the comprehensive performance and reliability of the roller ring. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a bainite high-carbon semi-steel centrifugal composite roller ring, which solves the problem of poor wear resistance and short life of the high-carbon semi-steel centrifugal composite roller ring in the prior art due to insufficient hardness and strength of the pearlite matrix structure.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: a bainite high carbon semi-steel centrifugal composite roller ring, comprising the following steps: Treat the mold used for centrifugal casting to adapt it to the molding and demoulding requirements of high-temperature molten steel pouring; Melting molten steel to a chemical composition range that satisfies the formation of bainite structure, and controlling the temperature and composition ratio of the molten steel; Molten steel is poured into a high-speed rotating mold, and a composite structure with inner and outer layers metallurgically bonded is obtained through the action of centrifugal force; The cast roller ring is heated, cooled and tempered, and the working layer matrix structure is mainly bainite by controlling the temperature and time; The heat treated roller rings are machined and their performance is verified to meet the requirements through microstructure, hardness and strength tests.
[0007] Preferably, the mold treatment includes coating the inner surface of the mold with a fire-resistant anti-adhesion coating having a thickness of 3 to 5 mm, and drying at 150 to 300° C. for 2 to 4 hours.
[0008] Preferably, the chemical composition of the molten steel includes: Carbon (C): 1.3% to 2.1%; Silicon (Si): 0.2% to 1.0%; Manganese (Mn): 0.4% to 1.5%; Chromium (Cr): 0.5% to 3.0%; Nickel (Ni): 3.0% ~ 4.5%; Molybdenum (Mo): 0.5% to 1.2%.
[0009] Preferably, the tapping temperature of the molten steel is 1450-1550°C, and the pouring temperature is 1400-1500°C.
[0010] Preferably, the rotation speed of the centrifuge is 800-1200 rpm, and the pouring speed of the molten steel is 1.0-5.0 kg / s.
[0011] Preferably, the heat treatment comprises the following steps: Heat the roller ring to 880-1100°C and keep it warm for more than 10 hours; Cool to 300-500°C and keep warm for 2-10 hours; Heat the roller ring to 500-650°C and keep it warm for more than 8 hours, and then slowly cool it to below 200°C.
[0012] Preferably, the cooling method to 300-500° C. is water cooling, air cooling or mist cooling, or a combination of two or more thereof.
[0013] Preferably, the mechanical processing of the heat-treated roller ring includes turning, grinding and polishing, and the final processing accuracy is controlled within 0.04 to 1 mm.
[0014] Preferably, the detection comprises the following steps: Use a microscope to examine the metallographic structure of the roller ring working layer and confirm that the bainite ratio is not less than 50%; Test the tensile strength of the roller ring and confirm that the tensile strength is not less than 650MPa; Check the hardness of the working layer and confirm that it is within the range of 55 to 75 HSD.
[0015] The present invention provides a bainite high carbon semi-steel centrifugal composite roller ring. It has the following beneficial effects: 1. The present invention adopts a chemical composition optimization design scheme, and ensures the purity and composition uniformity of molten steel by accurately adjusting the content of alloy elements such as carbon, silicon, manganese, chromium, nickel, and molybdenum, and controlling the quality of raw materials, and meets the formation requirements of a matrix structure mainly composed of bainite. Compared with the high-carbon semi-steel roller ring with pearlite matrix structure in the prior art, it solves the problem of low strength and wear resistance, and improves the tensile strength and hardness of the roller ring.
[0016] 2. The present invention adopts a centrifugal casting process, and by controlling the pouring speed of molten steel and the rotation speed of the centrifuge, the uniform distribution and metallurgical bonding of the molten steel in the working layer and the supporting layer during high-speed rotation are achieved, thereby achieving a dense and defect-free composite structure. Compared with the problems of delamination defects and poor metallurgical bonding that may be caused by improper centrifugal casting parameters in the prior art, the shortcomings of low bonding strength of the composite layer and many internal defects are solved.
[0017] 3. The present invention adopts a precise heat treatment process of austenitizing heating, bainite transformation cooling and tempering treatment. By reasonably controlling the austenitizing temperature, bainite transformation temperature and tempering temperature, a metallographic structure mainly composed of bainite is achieved. Compared with the problem that traditional high-carbon semi-steel materials in the prior art are prone to produce coarse pearlite or martensite due to improper heat treatment, the problems of unstable metallographic structure and insufficient wear resistance are solved, and the service life and impact resistance of the roller ring are greatly improved.
[0018] 4. The present invention adopts precision machining and systematic performance testing scheme, and ensures the roller ring size accuracy, hardness uniformity and strength stability through rough machining, fine machining, microstructure analysis, hardness testing, strength testing and other means, and meets the high reliability requirements in actual use. Compared with the problem of high failure rate of roller rings in use due to insufficient machining accuracy and single testing means in the prior art, the shortcomings of short service life and unstable quality are solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 , an embodiment of the present invention provides a bainite high carbon semi-steel centrifugal composite roller ring, comprising the following steps: S1, treating a casting mold used for centrifugal casting to adapt it to the molding and demoulding requirements of high temperature molten steel pouring; In this embodiment, the processing of the mold includes the structural design of the mold, the coating and the drying process after the coating, and the specific steps are as follows: In terms of mold structure design: the mold is made of metal (such as cast iron or heat-resistant alloy steel) to ensure that it has sufficient strength and resistance to thermal deformation under the action of high-temperature molten steel. The inner cavity of the mold is precisely processed according to the size and shape of the target roller ring, and its surface roughness is controlled within 0.8μm to improve the adhesion and coating quality of the paint; Specifically, the deviation between the mold cavity size and the target roll ring size is controlled within the range of 0.04 to 0.06 mm, which is mainly used to compensate for the shrinkage of the molten steel after cooling. The design of the cavity also includes the necessary pouring system (such as gates and risers) and exhaust system to ensure that the molten steel can evenly fill the entire cavity under the action of centrifugal force and reduce gas residue during the cooling process.
[0022] As an option, the end cover of the casting is treated with sand hanging to form a granular rough structure on the surface of the end cover, which can further improve the adhesion of the coating and enhance the guiding effect of the cavity wall on the flow of molten steel during the pouring process.
[0023] In terms of coating: In this embodiment, a layer of fire-resistant anti-adhesion coating is coated on the inner surface of the mold to prevent high-temperature molten steel from adhering to the mold surface and improve the surface finish of the casting. The coating is mainly made of aluminum silicate as the base material, supplemented with a certain proportion of heat-resistant binder and anti-cracking additives, so that it has good thermal shock resistance and adhesion; Specifically, the coating is formulated with the following ingredients: Aluminosilicate particles (average particle size 10-50 μm, accounting for 65%-80% of the coating mass) are used to provide fire resistance to the coating; Heat-resistant binder (such as water glass, accounting for 10% to 15% of the coating mass) is used to enhance the adhesion between the coating and the metal cavity surface; Anti-crack additives (such as zirconium oxide or magnesium oxide, accounting for 5% to 10% of the coating mass) are used to improve the crack resistance of the coating and prevent cracks from occurring at high temperatures; In some embodiments, the coating is applied by spraying, and the coating is evenly sprayed on the inner cavity surface of the mold, and the coating thickness is controlled within the range of 3 to 5 mm; In terms of drying after coating: In this embodiment, the coated casting is dried in the range of 150-300°C to remove moisture from the coating and ensure that the coating will not produce pores or cracks due to moisture volatilization during the pouring process.
[0024] Specifically, the mold is kept at a constant temperature in the drying furnace for 2 to 4 hours. During the drying process, the temperature changes on the surface and inside of the coating are monitored by thermocouples to ensure that the coating is completely dry. In addition, in order to prevent the coating from falling off during the drying process, the drying process usually adopts a gradual heating method from room temperature to the target drying temperature (such as 250°C), and the heating rate is controlled at 10 to 20°C / minute.
[0025] In terms of mold installation: after drying, the mold is assembled on the centrifuge and fixed with bolts and clamps to ensure the stability of the mold during high-speed rotation. The rotation speed of the centrifuge is adjusted to 800-1200rpm according to the mold size and the target molten steel pouring amount. During the installation of the mold, special attention should be paid to the following: The central axis of the centrifuge must be consistent with the geometric center of the mold, and the deviation should be controlled within 0.1mm to avoid uneven distribution of molten steel; After the mold is installed, it needs to pass a balance test to ensure that the centrifuge rotates without obvious vibration.
[0026] In a possible implementation, the surface roughness of the inner cavity of the casting mold can be further optimized by an electrolytic polishing process, and the roughness can be reduced to within 0.2 μm to meet the requirements of high-precision casting surface quality.
[0027] The composition ratio of the coating can also be adjusted according to the specific casting size and the molten steel pouring temperature. For example, when the target molten steel pouring temperature is higher than 1500°C, the proportion of anti-cracking additives (such as zirconium oxide) can be appropriately increased to 15% to further improve the coating's resistance to thermal shock.
[0028] In addition, in some embodiments, metal ceramic particles (such as aluminum oxide or silicon carbide) may be added to the coating to further improve the wear resistance of the casting surface through the design of the composite coating; S2, smelting the molten steel to a chemical composition range that satisfies the formation of bainite structure, and controlling the temperature and composition ratio of the molten steel; the molten steel smelting step S2 is an important step in the preparation of bainite high-carbon semi-steel centrifugal composite roller rings of the present invention, and its purpose is to obtain high-carbon semi-steel materials that meet the formation of bainite matrix structure through smelting, while ensuring the uniformity and purity of the molten steel composition, and providing a high-quality molten steel source for subsequent centrifugal casting; In this embodiment, the smelting of molten steel is achieved through the following aspects: selection of smelting equipment, adjustment of chemical composition, degassing and purification treatment, and temperature control; In terms of the selection of smelting equipment: In this embodiment, a medium frequency furnace or an electric arc furnace is used to melt molten steel. The power of a medium frequency furnace is generally 500-5000kW, which is suitable for rapid melting of high-carbon steel and its alloy components, and has the advantages of fast melting speed and precise temperature control; an electric arc furnace can be further used for melting high-carbon steel grades, especially when refining treatment is required, which can significantly reduce the impurity content.
[0029] Specifically, the interior of the furnace body needs to be lined with high-aluminum refractory materials with a refractoriness of not less than 1700°C to ensure that the inner wall of the furnace body can resist high-temperature erosion of the molten steel. In some embodiments, in order to improve the temperature uniformity of the molten steel, an electromagnetic stirring device is installed in the furnace during the smelting process to uniformly stir the molten steel through eddy currents generated by electromagnetic induction.
[0030] In terms of chemical composition adjustment: In this embodiment, the chemical composition of the molten steel is precisely proportioned to meet the requirements of bainite structure formation. Specifically, the ratio of each element in the molten steel is: Carbon (C): 1.3% to 2.1%, providing sufficient hardness and strength; Silicon (Si): 0.2% to 1.0%, promotes bainite transformation and improves matrix strength; Manganese (Mn): 0.4% to 1.5%, increases the hardenability of steel; Chromium (Cr): 0.5% to 3.0%, refines carbides and improves wear resistance; Nickel (Ni): 3.0% to 4.5%, stabilizes bainite structure and improves toughness; Molybdenum (Mo): 0.5% to 1.2%, inhibits pearlite transformation and improves wear resistance.
[0031] In some embodiments, the specific ratio of the chemical components can be appropriately adjusted according to the actual size and use conditions of the roller ring. For example, when the target roller ring needs to withstand high impact loads, the content of nickel and manganese can be appropriately increased to improve toughness; In one possible implementation, in order to ensure the accuracy of the chemical composition, the alloy element content of the molten steel is monitored in real time during the smelting process through sampling analysis (such as spectral analysis), and the composition is adjusted by adding pre-formulated alloy powder (such as Fe-Cr alloy or Fe-Mo alloy) when necessary.
[0032] In terms of temperature control: In this embodiment, the tapping temperature of the molten steel is controlled at 1450-1550°C, and the pouring temperature is controlled at 1400-1500°C, to ensure that the molten steel maintains good fluidity and solidification properties during the centrifugal casting process; Specifically, too high a temperature may cause segregation in the casting, while too low a temperature may affect the filling capacity of the molten steel. Therefore, after steel is tapped, the temperature of the molten steel is monitored in real time by a thermocouple, and the temperature is precisely adjusted by adjusting the furnace power when necessary; In some embodiments, in order to slow down the temperature loss of molten steel, the molten steel after tapping can be secondarily insulated by a heat preservation bag, the inner lining of which is made of high-aluminum heat-insulating material, and the heat-insulating efficiency of which is not less than 85%; In a possible implementation, a trace amount of rare earth elements (such as Ce or La) may be introduced during the smelting process of molten steel, and the rare earth elements react with inclusions to form stable compounds (such as rare earth oxides or sulfides), thereby further refining the grains of the casting and improving its mechanical properties. In addition, in order to improve the cleanliness and smelting efficiency of molten steel, an atmosphere protection smelting process may be introduced in some embodiments. For example, a sealing cover is provided above the electric arc furnace to isolate the air by filling inert gas to prevent oxidation of the molten steel during the smelting process. S3, injecting molten steel into a high-speed rotating mold, and obtaining a composite structure with inner and outer layers metallurgically bonded by centrifugal force; The centrifugal casting step S3 of molten steel is the core process of preparing bainite high-carbon semi-steel centrifugal composite roller rings of the present invention. Through the high-speed rotating mold and the fluidity and distribution behavior of molten steel under the action of centrifugal force, a composite roller ring with a dense working layer and a supporting layer structure and good metallurgical bonding is obtained. In this embodiment, the centrifugal casting of molten steel is achieved through the following aspects: the pouring method of molten steel, the speed control of the centrifuge, the cooling and demoulding of the casting; In terms of the pouring method of molten steel: In this embodiment, the molten steel flows from the ladle into the inner cavity of the high-speed rotating mold. The pouring process needs to ensure that the molten steel fills the mold evenly and avoids turbulence as much as possible. To this end, the molten steel pouring adopts a combination of step-by-step pouring and runner guide technology; Specifically, the molten steel is introduced into the inner cavity of the mold step by step through the tundish, and the pouring rate is controlled within the range of 1.0 to 5.0 kg / s. A pouring rate that is too low may result in insufficient filling of the molten steel, while a pouring rate that is too high may easily generate turbulence, affecting the distribution of the molten steel and the metallurgical bonding effect. In some embodiments, the pouring system adopts an inclined pouring port design so that the molten steel enters the mold cavity in a nearly smooth streamlined form, reducing the entrainment of inclusions during the pouring process.
[0033] In one possible implementation, a layer of covering agent (such as a fluoride salt mixture) can be sprinkled on the surface of the molten steel before pouring. The function of the covering agent is to further isolate the contact between the surface of the molten steel and the air, reduce the formation of an oxide layer, and be introduced into the filter through the flow channel during the pouring process, thereby effectively removing oxide inclusions on the surface of the molten steel.
[0034] In terms of the speed control of the centrifuge: In this embodiment, the rotation speed of the centrifuge is precisely controlled between 800 and 1200 rpm according to the mold size, the weight of the molten steel and the design requirements of the target roller ring. The control of the centrifuge speed directly determines the distribution behavior of the molten steel in the mold cavity and the intensity of the centrifugal force. The formula is as follows: Where: F is the centrifugal force, in Newton (N); m is the mass of the molten steel, in kilograms (kg); v is the linear velocity of the molten steel in the cavity, in meters per second (m / s), which is determined by the rotation speed and radius; r is the radius of the cavity, in meters (m); In general, the centrifugal force needs to be large enough to ensure that the molten steel can fully adhere to the inner wall of the cavity, but excessive centrifugal force may cause segregation. In a possible implementation method, the start-up and acceleration of the centrifuge are controlled in a step-by-step manner to avoid splashing of the molten steel due to inertia at the initial stage of rotation; S4, heating, cooling and tempering the cast roller ring, and controlling the temperature and time to make the matrix structure of the working layer mainly bainite; Heat treatment step S4 is an important step in the preparation of bainite high carbon semi-steel centrifugal composite roller rings of the present invention. Its purpose is to optimize the metallographic structure after casting through reasonable heating, cooling and tempering processes, so that the roller ring working layer is mainly composed of bainite matrix structure, thereby achieving the comprehensive performance of high hardness, high strength and good wear resistance; In this embodiment, the roller ring after casting is first subjected to austenitization heating treatment to achieve uniformity and complete austenitization of the working layer grains. Specifically, the roller ring is placed in a heating furnace for heating, the heating temperature is controlled at 880-1100°C, and the insulation time is not less than 10 hours; Specifically, the uniformity of the temperature in the furnace during the heating process is critical. In order to avoid local overburning or coarse grains caused by temperature differences, in some embodiments, multi-point thermocouples are used to monitor the temperature distribution in the furnace in real time, and the temperature uniformity is maintained by adjusting the power of the heating elements in the furnace; As an option, the heating rate can be adjusted according to the size and weight of the roller ring. For example, for a roller ring with a larger diameter, the heating rate is usually controlled at 5-10°C / hour to avoid thermal stress cracking caused by excessive temperature gradient; In the bainite transformation cooling stage: In this embodiment, after the austenitizing heating is completed, the roller ring is taken out of the heating furnace and quickly cooled to 300-500°C, which is the optimal range for the transformation of austenite to bainite. The cooling method can be water cooling, air cooling or mist cooling, and the specific selection needs to be determined according to the roller ring size and cooling uniformity requirements; In general, the control of cooling rate is the key to ensure bainite transformation. The cooling rate can be estimated by the following formula: Where: q is the cooling rate (℃ / second); k is the radiation heat transfer coefficient (W / m 2 ·K); A is the heat dissipation surface area of the roller ring (m 2 );T melt is the austenitizing temperature (℃); T env is the ambient temperature of the cooling medium (℃); m is the mass of the roller ring (kg); c is the specific heat capacity of the roller ring material (J / kg·K); Specifically, during the cooling process, it is necessary to ensure that the temperature gradient between the roller ring working layer and the supporting layer is small to avoid the stratification phenomenon at the interface between the inner and outer layers. In some embodiments, in order to further improve the cooling uniformity, a zone cooling technology can be used, that is, the flow rate of the cooling medium in different parts is adjusted to achieve a uniform distribution of the temperature field; In one possible implementation, in order to reduce the risk of martensite formation, the temperature can be maintained in the range of 300-500°C for not less than 2 hours by controlling the cooling rate during the cooling process to ensure the complete transformation of austenite to bainite; in the tempering stage: after cooling, the roller ring needs to be tempered to eliminate the residual stress generated during the heat treatment process and improve the toughness of the material. In this embodiment, the cooled roller ring is placed back in the heating furnace and heated to 500-650°C for not less than 8 hours; Specifically, the tempering process adopts a slow heating and furnace cooling method to further optimize the bainite matrix structure. In some embodiments, in order to improve the heating efficiency, a circulating fan can be installed in the furnace to accelerate the temperature uniformity of the roller ring surface and the interior through convection heat transfer; In one possible implementation, the roller ring needs to be slowly cooled to below 200°C in the furnace after tempering, and the cooling rate is controlled at 5-30°C / hour to avoid new thermal stress due to too fast cooling; To further improve the accuracy and efficiency of the heat treatment, in some embodiments, an automated control system may be used to monitor and adjust the entire heat treatment process in real time. Specifically, an industrial-grade PLC (programmable logic controller) may be used to connect thermocouples, infrared thermometers, and cooling medium flow meters to achieve closed-loop control of temperature and time parameters; In addition, the austenitizing temperature and tempering temperature can be optimized for roller rings of different specifications. For example, for small-sized roller rings, the austenitizing temperature can be appropriately lowered (such as controlled at 900-950°C) to shorten the insulation time and improve production efficiency; in another possible implementation, a low-temperature tempering process (300-400°C) can be introduced to further improve the wear resistance of the roller ring surface while maintaining its hardness unchanged; S5. Machining the heat-treated roller ring and verifying that its performance meets the requirements through microstructure, hardness and strength tests; The mechanical processing and performance testing step S5 is the final step of preparing the bainite high carbon semi-steel centrifugal composite roller ring of the present invention, and its purpose is to process the heat-treated roller ring to a size and shape that meets the use requirements through precise mechanical processing technology, and at the same time verify whether the comprehensive performance of the roller ring meets the technical indicators through microstructure analysis, hardness and strength and other performance tests; In this embodiment, the roller ring after heat treatment is first rough-machined, and then fine-machined to achieve the target size and surface accuracy; specifically, the rough-machined step includes removing the oxide scale and excess blank residue formed during the heat treatment process to ensure the surface is flat and provide a good foundation for fine machining. In some embodiments, rough machining uses a CNC lathe or special turning equipment to remove 3 to 8.0 mm of the roller ring surface by turning. The surface roughness of the roller ring after rough machining is generally controlled within the range of Ra3.2 to 6.3 μm; The finishing step is completed by high-precision CNC machine tools, and its main purpose is to achieve the target dimensional accuracy and surface roughness optimization. As an option, finishing uses carbide tools or CBN tools for cutting to ensure that the machined surface is free of burrs and scratches. After finishing, the dimensional tolerance of the roller ring is controlled within 0.04-0.06mm, and the surface roughness is controlled within the range of Ra0.8-1.6μm; In some embodiments, a grinding process may be added after fine machining to further reduce the surface roughness to Ra0.4-0.8 μm by a precision grinder, while improving the roundness and concentricity of the roller ring; In terms of microstructure detection: In this embodiment, the microstructure of the working layer of the roller ring is analyzed by a metallographic microscope to verify whether the proportion of its bainite matrix structure meets the technical indicators. Specifically, the steps of microstructure detection are as follows: First, a sample is cut from the working layer of the roller ring. The sample needs to cover the inner layer, middle layer and outer layer of the roller ring to ensure the comprehensiveness of the structure analysis. Then the sample is metallographically prepared, including mechanical polishing and chemical etching. The etching agent formula is usually 4% nitric acid ethanol solution; Under a microscope, observe and count the area distribution ratio of bainite structure. Generally, the proportion of bainite in the working layer should be no less than 50%, and the carbides should be evenly distributed and the total amount should not exceed 20%. In some embodiments, the microstructure can be quantitatively analyzed by image analysis software to improve the accuracy of the statistical results; In terms of hardness detection: In this embodiment, a Shore hardness tester is used to measure the hardness distribution of the roller ring working layer, and the measuring points need to cover the entire working layer to ensure the uniformity of the hardness distribution; Specifically, the hardness of the working layer should be controlled within the range of 55 to 75 HSD, which can meet the high hardness wear resistance requirements and ensure appropriate toughness and impact resistance. In some embodiments, in order to verify the uniformity of hardness in different areas, a microhardness tester can also be used to perform more accurate hardness measurements on local areas (such as bainite and carbide distribution areas); In a possible implementation, the working layer may also be subjected to a gradient hardness test, that is, a point-by-point hardness test is performed from the surface of the working layer to the inside of the supporting layer to confirm whether the hardness transition between the working layer and the supporting layer is smooth, so as to avoid early failure caused by a sudden change in hardness; In terms of strength testing: In this embodiment, the tensile strength of the roller ring material is tested by a tensile test to verify whether its bearing capacity meets the design requirements; Specifically, a standard specimen is prepared by sampling from the working layer of the roller ring. The specimen is machined into a tensile specimen and then placed on a universal testing machine for a tensile test. The tensile strength is calculated as follows: Where: b is the tensile strength, in MPa; F is the maximum tensile force, in Newton (N); A is the cross-sectional area of the sample, in square meters (m 2 ); Generally, the tensile strength of the working layer should be no less than 650 MPa. In some embodiments, the toughness and impact resistance of the material can be further verified by impact testing, and the test temperature range is usually 0°C to room temperature; In one possible implementation, ultrasonic nondestructive testing can be performed on the roller ring before the final performance test to confirm whether the metallurgical bonding between the working layer and the supporting layer is good, and whether there are defects such as pores and cracks inside. The testing frequency is usually set to 1 to 5 MHz, and the appropriate probe is selected according to the size and thickness of the roller ring; In addition, in some embodiments, the roller ring can be subjected to fatigue tests under simulated service conditions, and the fatigue life of the material can be tested by periodic load. The load frequency of the fatigue testing machine is generally controlled at about 10 Hz, and the number of test cycles can reach 10. 6 More than times.
[0035] Example 1: Preparation method of bainite high carbon semi-steel centrifugal composite roller ring suitable for general H-beam rolling mill Step 1: Mold Preparation The casting mold is a metal mold made of high-strength cast iron. The surface of the cavity is sprayed with 4mm thick aluminosilicate refractory coating. The coating formula is: 70% aluminosilicate particles, 15% water glass, 10% zirconium oxide, and 5% anti-cracking agent.
[0036] The coated mold was dried at 200°C for 3 hours and then assembled on a centrifuge with a rotation speed set to 1000 rpm and dynamic balancing performed to ensure operational stability.
[0037] Step 2: Molten Steel Melting When melting molten steel in a medium frequency furnace, the controlled composition is as follows: Carbon (C): 1.8%, Silicon (Si): 0.6%, Manganese (Mn): 1.2%, Chromium (Cr): 1.8%, Nickel (Ni): 4.0%, Molybdenum (Mo): 0.8%.
[0038] The melting temperature is 1520℃, and the molten steel is vacuum degassed to control the oxygen content below 12ppm.
[0039] Step 3: Centrifugal Casting The molten steel is injected into the high-speed rotating mold at a speed of 3.0kg / s. Under the action of centrifugal force, the steel quickly adheres to the inner wall of the mold cavity. After the filling is completed, it is naturally cooled to 400℃ and then demolded. Circulating water is introduced in the initial cooling stage to enhance cooling and ensure cooling uniformity.
[0040] Step 4: Heat Treatment The roller ring is heated to 950℃ in an electric heat treatment furnace and kept at this temperature for 12 hours for austenitization. It is then rapidly cooled to 450℃ and kept at this temperature for 3 hours to promote bainite transformation, and finally tempered to 600℃ and kept at this temperature for 8 hours before being cooled in the furnace to below 200℃.
[0041] Step 5: Machining and performance testing After rough machining on a CNC lathe to remove 5mm of excess, fine machining is performed. The final machining accuracy is controlled at ±0.05mm and the surface roughness is Ra1.2μm.
[0042] The test results show that: The metallographic structure contains 55% bainite and 15% carbide. The hardness of the working layer is 60HSD and the tensile strength is 670MPa; The service life is 40% longer than that of traditional pearlite semi-steel.
[0043] Example 2: Roller ring suitable for high-load rolling conditions Step 1: Mold Preparation The casting mold is made of heat-resistant steel. The surface of the cavity is electrolytically polished and then sprayed with alumina-based refractory coating. The coating thickness is 3mm. 10% silicon carbide particles are added to the refractory coating to improve wear resistance.
[0044] After coating, the mold was dried at 250°C for 2 hours with the centrifuge speed set at 1200 rpm.
[0045] Step 2: Molten Steel Melting Molten steel is melted in an electric arc furnace with the chemical composition: Carbon (C): 2.0%, Silicon (Si): 0.5%, Manganese (Mn): 1.5%, Chromium (Cr): 2.5%, Nickel (Ni): 3.5%, Molybdenum (Mo): 1.0%.
[0046] The molten steel melting temperature is 1500℃, and argon gas is used to protect the melting to avoid oxidation.
[0047] Step 3: Centrifugal Casting Molten steel is injected into the rotating mold at a rate of 2.5kg / s, and the centrifuge speed is 1200rpm. After molding, it is quickly cooled to 350℃ and demolded. During the cooling process, cooling water is introduced into the outside of the cavity to control the cooling rate and ensure uniform thickness of the working layer and the supporting layer.
[0048] Step 4: Heat Treatment The roller ring is heated to 1050℃, kept at this temperature for 10 hours to austenitize, then cooled to 400℃, kept at this temperature for 4 hours to achieve bainite transformation. It is then tempered and heated to 550℃ at a rate of 10℃ / min, kept at this temperature for 10 hours, and then slowly cooled to 150℃.
[0049] Step 5: Machining and performance testing The rough machining allowance is 1.0mm, and the surface roughness Ra after fine machining is 0.8μm. The test shows: The metallographic structure contains 60% bainite and 18% carbide. The hardness is 68HSD and the tensile strength is 700MPa; The wear resistance is 50% higher than that of pearlite matrix, and the service life is extended by 2 times in high-load rolling.
[0050] Example 3: Rapid preparation of small-sized roller rings Step 1: Mold Preparation The casting mold is made of high-strength aluminum alloy, and the cavity is sprayed with a composite coating (20% zirconium oxide particles, 50% aluminum silicate, 10% water glass, 20% anti-cracking agent), with a coating thickness of 5mm.
[0051] After coating, the mold was dried at 200°C for 4 hours with the centrifuge speed set at 900 rpm.
[0052] Step 2: Molten Steel Melting Molten steel is smelted in a medium frequency furnace, and its chemical composition is: Carbon (C): 1.6%, Silicon (Si): 0.7%, Manganese (Mn): 0.8%, Chromium (Cr): 1.0%, Nickel (Ni): 4.5%, Molybdenum (Mo): 0.6%.
[0053] The smelting temperature is 1480°C, and a vacuum degassing process is used to remove gas inclusions, and the oxygen content is controlled below 10ppm.
[0054] Step 3: Centrifugal Casting The molten steel was injected into the rotating mold at a rate of 1.5 kg / s, the centrifuge speed was 900 rpm, and the mold was demoulded after cooling to 300 °C. After demoulding, slow cooling was performed to reduce thermal stress.
[0055] Step 4: Heat Treatment The roller ring was heated to 900°C, kept at this temperature for 8 hours to austenitize, rapidly cooled to 450°C and kept at this temperature for 2 hours to transform into bainite, and then tempered to 500°C, kept at this temperature for 6 hours, and then cooled to room temperature.
[0056] Step 5: Machining and performance testing The surface roughness of the roller ring after processing is Ra1.0μm, and the test shows: The metallographic structure contains 50% bainite and 15% carbide. The hardness is 58HSD and the tensile strength is 660MPa; Roller rings are suitable for small rolling mills and their service life is increased by 30%.
[0057] Example 4: Composite roller ring with high corrosion resistance Step 1: Mold Preparation The casting mold is made of alloy steel, and the cavity is sprayed with a composite refractory coating with a thickness of 3mm (80% aluminum oxide, 10% titanium oxide, and 10% magnesium oxide).
[0058] After coating, the mold was dried at 200°C for 3 hours with the centrifuge speed set at 1000 rpm.
[0059] Step 2: Molten Steel Melting Molten steel is melted in an electric arc furnace with the chemical composition: Carbon (C): 1.5%, Silicon (Si): 0.4%, Manganese (Mn): 1.0%, Chromium (Cr): 3.0%, Nickel (Ni): 4.0%, Molybdenum (Mo): 1.0%.
[0060] The molten steel melting temperature is 1520℃, and the melting is protected by argon gas.
[0061] Step 3: Centrifugal Casting Molten steel was poured into the mold at a rate of 3.0 kg / s, the centrifuge speed was 1000 rpm, cooled to 350 °C and then slowly cooled to 200 °C after demoulding.
[0062] Step 4: Heat Treatment The roller ring is heated to 950°C, kept at this temperature for 10 hours for austenitization, cooled to 450°C and kept at this temperature for 4 hours, then tempered to 600°C, kept at this temperature for 8 hours and then cooled to 150°C.
[0063] Step 5: Machining and performance testing The surface roughness Ra after processing is 1.0μm, and the test results show: The metallographic structure contains 58% bainite and 16% carbide. The hardness is 62HSD and the tensile strength is 680MPa; The roller ring has excellent corrosion resistance and is suitable for rolling conditions in corrosive media.
[0064] Comparative Example 1: Comparison with Example 1 Preparation process: The parameters of mold preparation, molten steel smelting and centrifugal casting are the same as those in Example 1.
[0065] During the cooling stage of heat treatment, the austenitized roller ring was directly cooled to 200°C, and the temperature was not controlled in the bainite transformation range of 300-500°C.
[0066] Difference from Example 1: In Comparative Example 1, the heat treatment cooling temperature range is changed so that the cooling does not stay in the optimal range of bainite transformation (300-500°C), while Example 1 accurately controls the temperature range. The comparison between the two verifies the influence of the cooling temperature in the bainite transformation stage on the structure and performance.
[0067] Comparative Example 2: Comparison with Example 2 Preparation process: The casting mold preparation and molten steel smelting are the same as in Example 2.
[0068] During the centrifugal casting stage, the centrifuge speed was reduced to 500 rpm (lower than 1200 rpm in Example 2).
[0069] Difference from Example 2: In Comparative Example 2, the centrifuge speed is significantly reduced, resulting in insufficient centrifugal force, which may affect the distribution of molten steel in the cavity and the bonding effect of the composite layer. Example 2 ensures the uniformity and metallurgical bonding of the working layer and the supporting layer through a reasonable speed. The comparison between the two verifies the importance of speed selection to the quality of the composite structure.
[0070] Comparative Example 3: Comparison with Example 3 Preparation process: The process parameters of mold preparation, centrifugal casting and heat treatment are the same as those in Example 3.
[0071] When molten steel is smelted, the chemical composition is adjusted to a low alloy design (such as the nickel content is reduced from 4.5% to 2.0%, and the molybdenum content is reduced from 0.6% to 0.3%).
[0072] Difference from Example 3: Comparative Example 3 reduces the alloying element content in the molten steel, especially nickel and molybdenum, which may lead to a decrease in the proportion of bainite structure and a decrease in hardness. Example 3 adopts an optimized high-alloy composition design to ensure the formation of bainite and the improvement of overall performance. The comparison between the two verifies the importance of chemical composition optimization.
[0073] Comparative Example 4: Comparison with Example 4 Preparation process: The parameters of mold preparation, molten steel smelting and centrifugal casting are the same as those in Example 4.
[0074] The temperature of the heat treatment tempering stage is reduced from 600℃ to 400℃.
[0075] Difference from Example 4: Comparative Example 4 lowers the tempering temperature, which may result in incomplete elimination of tempering stress and insufficient toughness, while Example 4 uses a higher tempering temperature (600°C) to effectively balance hardness and toughness. The comparison between the two verifies the influence of tempering temperature selection on organizational stability and impact resistance.
[0076] Comparative Example 5: Comparison with Example 1 Preparation process: The refractory coating formula was adjusted during mold preparation to reduce the aluminosilicate content and increase the alumina proportion (30%).
[0077] The parameters of molten steel smelting, centrifugal casting and heat treatment are the same as those in Example 1.
[0078] Difference from Example 1: The coating formula in Comparative Example 5 is changed, which may reduce the high temperature resistance and adhesion of the coating, thereby affecting the surface quality and demolding effect of the casting. Example 1 adopts an optimized coating formula to ensure the surface finish and casting stability of the casting. The comparison between the two verifies the necessity of coating optimization for casting performance.
[0079] Comparative Example 6: Comparison with Example 2 Preparation process: No vacuum degassing treatment was carried out during the steel smelting stage.
[0080] The parameters of mold preparation, centrifugal casting and heat treatment are the same as those in Example 2.
[0081] Difference from Example 2: Comparative Example 6 omits the vacuum degassing process, which may result in higher oxygen content and inclusions in the molten steel, thereby affecting the purity and mechanical properties of the microstructure. Example 2 improves the purity of the molten steel through vacuum degassing. The comparison between the two verifies the role of the degassing process in performance control.
[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A bainite high carbon semi-steel centrifugal composite roller ring, characterized in that: The following steps are involved: Treat the mold used for centrifugal casting to adapt it to the molding and demoulding requirements of high-temperature molten steel pouring; Melting molten steel to a chemical composition range that satisfies the formation of bainite structure, and controlling the temperature and composition ratio of the molten steel; Molten steel is poured into a high-speed rotating mold, and a composite structure with inner and outer layers metallurgically bonded is obtained through the action of centrifugal force; The cast roller ring is heated, cooled and tempered, and the working layer matrix structure is mainly bainite by controlling the temperature and time; The heat treated roller rings are machined and their performance is verified to meet the requirements through microstructure, hardness and strength tests.
2. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The mold treatment comprises coating the inner surface of the mold with a fire-resistant anti-adhesion coating having a thickness of 3 to 5 mm, and drying the coating at 150 to 300° C. for 2 to 4 hours.
3. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The chemical composition of the molten steel includes: Carbon: 1.3%~2.1%; Silicon: 0.2%~1.0%; Manganese: 0.4% to 1.5%; Chromium: 0.5% to 3.0%; Nickel: 3.0% to 4.5%; Molybdenum: 0.5%~1.2%.
4. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The tapping temperature of the molten steel is 1450-1550°C, and the pouring temperature is 1400-1500°C.
5. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The rotation speed of the centrifuge is 800-1200 rpm, and the pouring speed of the molten steel is 1.0-5.0 kg / s.
6. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The heat treatment comprises the following steps: Heat the roller ring to 880-1100°C and keep it warm for more than 10 hours; Cool to 300-500°C and keep warm for 2-10 hours; Heat the roller ring to 500-650°C and keep it warm for more than 8 hours, and then slowly cool it to below 200°C.
7. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The cooling method to 300-500° C. is water cooling, air cooling or mist cooling, or a combination of two or more thereof.
8. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The mechanical processing of the heat-treated roller ring includes turning, grinding and polishing, and the final processing accuracy is controlled within 0.04 to 1 mm.
9. The bainite high carbon semi-steel centrifugal composite roller ring according to claim 1, characterized in that: The detection comprises the following steps: Use a microscope to examine the metallographic structure of the roller ring working layer and confirm that the bainite ratio is not less than 50%; Test the tensile strength of the roller ring and confirm that the tensile strength is not less than 650MPa; Check the hardness of the working layer and confirm that it is within the range of 55 to 75 HSD.